TEACHER’S QUESTIONS USED IN TEACHING ENGLISH AT THE 1ST GRADE STUDENTS OF ONE JUNIOR HIGH SCHOOL IN BANDUNG - Gita Ernita; Tini Apriliani (IKIP Siliwangi, 2020)
Teachers are facilitators that assist students to make the learning process easier and more comfortale. Techer question is a part of learning process. The aim of this research is to find out the types of questions asked by teachers in teaching and learning process. This research is descriptive research. Participant of this research are two English teachers at SMP PGRI Bandung. The data collection used two instruments namely audio recording and note taking. From this research, researcher found that open ended questions are mostly occur in the classroom beside ; yes/no questions, short answer questions, display questions, referential questions and non retrieval questions. During research, there are three kind of languages used by teachers, they are English, mixed English –Indonesian, and Indonesian.